1989
DOI: 10.1097/00000658-198901000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Lymphoma. Is Surgery Mandatory for Diagnosis or Treatment?

Abstract: From 1982 to 1986, nine patients with non-Hodgkin's lymphoma primarily involving the pancreas were managed at the Johns Hopkins Medical Institutions. This group of nine patients represents 2.2% of patients with non-Hodgkin's lymphoma (nine of 402) and 4.9% of all patients presenting with pancreatic malignancies (nine of 182) at the Johns Hopkins Medical Institutions during this period. Computed tomography (CT) scan findings of a large pancreatic mass (6 cm) with extrapancreatic extension and significant retrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 18 publications
1
72
1
1
Order By: Relevance
“…The majority of patients with PPL can be managed without surgery and long-term disease remission can be obtained with chemotherapy alone. 2 The role of surgery in this setting is limited to rare occasions when FNA plus FC are nondiagnostic, and tissue diagnosis therefore is required. In 1 study of 10 patients with PPL, the mean survival was 13 months for patients who received chemotherapy alone (n ϭ 2), 22 months for patients treated with radiation therapy only (n ϭ 5), and 26 months for patients receiving combined radiation therapy and chemotherapy (n ϭ 3).…”
Section: Flow Cytometric Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients with PPL can be managed without surgery and long-term disease remission can be obtained with chemotherapy alone. 2 The role of surgery in this setting is limited to rare occasions when FNA plus FC are nondiagnostic, and tissue diagnosis therefore is required. In 1 study of 10 patients with PPL, the mean survival was 13 months for patients who received chemotherapy alone (n ϭ 2), 22 months for patients treated with radiation therapy only (n ϭ 5), and 26 months for patients receiving combined radiation therapy and chemotherapy (n ϭ 3).…”
Section: Flow Cytometric Findingsmentioning
confidence: 99%
“…Moreover, the majority of patients with PPL can be managed without surgery and long-term disease remission reportedly can be obtained with chemotherapy alone. 2 The role of surgery in this setting is limited to the rare occasions when initial FNA and FC analysis are nondiagnostic.…”
mentioning
confidence: 99%
“…However, in the past, this technique has been limited to providing cytological material only and therefore has been of limited application in lymphoma where morphological accuracy requires more substantial tissue, particularly to determine nodularity (Zornoza et al, 1981;Buscarini et al, 1985;Pontifex & Klimo, 1984;Webb et al, 1989 (Haaga, 1979;Staab et al, 1979;Husband & Golding, 1983;Ferrucci et al, 1980). Several authors have reported the use of guided biopsy in patients with Hodgkin's disease and non-Hodgkin's lymphoma, in particular using fine needle aspiration to provide material for cytological analysis (Zornoza et al, 1981;Buscarini et al, 1985;Pontifex & Klimo, 1984;Webb et al, 1989). The latter technique has the potential advantage of speed in making a diagnosis in the gravely ill patient but rarely provides adequate morphological information to fully characterise non-Hodgkin's lymphomas;…”
mentioning
confidence: 99%
“…Webb et al reported that PPLs comprised 4.6% of pancreatic neoplasms and 2.2% of non-Hodgkin's lymphoma cases (3). A literature review by Ji et al (4) indicated that diffuse large B-cell lymphoma was the most commonly reported histological type of PPL, and that patients were predominantly male.…”
Section: Discussionmentioning
confidence: 99%